Pengembangan Website Company Profile sebagai Media Publikasi dan Branding EEC Jombang - Andriani, Anita; Indana Lazulfa; Mufarrihah, Iftitaahul; Reza Augusta J.F. (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of information technology has encouraged educational institutions to adapt to digital transformation, particularly in the areas of information dissemination and institutional branding. Effective English Course (EEC) Jombang, as an English language training institution, had not yet possessed a digital information medium capable of reaching the wider community effectively. This community service activity aimed to develop a WordPress-based company profile website as a medium for publication and branding for EEC Jombang. The methods implemented included observation, needs analysis, website design, system implementation, and website management assistance. The resulting website successfully displayed institutional profile information, educational programs, tutor data, event documentation, galleries, and contact information in a more structured and accessible manner. The implementation results indicate that the website improved the institution’s digital image, facilitated information dissemination, and expanded promotional reach to the public. Therefore, the development of a company profile website can serve as an effective digital publication and branding strategy for educational institutions.